Radiotherapy and newly approved cancer drugs – A quantitative analysis of registered protocols for drugs approved for the treatment of solid tumors. (March 2022) - Rabe, Leonie; Wenz, Frederik; Ehmann, Michael; Lohr, Frank; Hofheinz, Ralf Dieter; Buergy, Daniel
Highlights: In 52.4% of drugs, no patient had received RT in a trial at the FDA approval date. In 92.9% of cancer drugs no drug/RT studies were published at the approval date. Drug/RT trials were mostly industry-sponsored but less common than drug-only trials. Clinicians must rely on postmarketing studies-/surveillance to assess RT/drug risks. Abstract: Background/purpose: To evaluate the usage of RT in trial protocols for anti-cancer drugs approved by the US Food and Drug Administration (FDA). Methods: Drugs which had been granted an FDA approval between 2010 and 2017 for the treatment of solid tumors in adults were identified. Use of RT in relation to each drug's approval date was reviewed on ClinicalTrials.gov. Results: Out of 42 drugs, none was initially approved for an indication which mandates RT. One drug (2.4%) has a post-approval label extension for sequential usage after RT. 5846 records were screened, exclusion of non-cancer trials and duplicates resulted in 4254 protocols out of which 2919 were industry-sponsored (68.6%). RT was tested in 350 (8.2%) studies. Out of 75 drug/RT trials which were initiated prior to approval, fourteen had not yet started recruitment, 45 were recruiting, one was completed, one prematurely terminated and fourteen fully-recruited but ongoing at approval time. Out of the fully-recruited or completed studies, results from four studies on three drugs were already published. In 52.4% of drugs, no patient had been treated with a drug/RT combination at the approval date. Drug/RT studies were less likely industry-sponsored ( p  < 0.001) and more likely initiated post-approval ( p  < 0.001) compared to drug-only trials. Despite this imbalance, pre-approval drug/RT trials were still mostly industry-sponsored (65.3%). Conclusion: No drug/RT data were publicly available in over 90% of newly approved anti-cancer drugs. These results indicate that clinicians must rely on postmarketing surveillance to identify drug/RT interactions as data from trials are unavailable at approval.